PHYSICAL AND MECHANICAL PROPERTIES OF THREE POLYSTYRENE IMPREGNATED INDONESIAN WOOD SPECIES - Nurwati Hadjib (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2005)
The disadvantage of fast-growing species is that they have inferior physical and mechanical properties. Polystyrene impregnation can be applied to improve physical and mechanical properties. Wood samples, which were dried until 10% moisture content were put into impregnating tank and vacuum pressured at 20-mm Hg for two hours. During the gradual release of vacuum, styrene monomers, vinyl acetate monomers and terburyl-peroxide catalyst was streamed into the tank. Afterwards, the pressure inside the tank was allowed to decrease to 500 mm Hg and kept for 60 minutes. Wood samples which had been impregnated were subsequently immersed in water, then wrapped in aluminum foils and put in the oven for 24 hours at 60°C. The samples were then tested for the polymer loading and their physical and mechanical properties. The results showed that the polymer loadings in wood plastics with the species of origin (i.e. consecutively sengon, pine and rubber wood) were 118%, 72% and 44%, respectively. Impregnation with polystyrene (copolymer of styrene and vinyl acetate monomers) could improve the physical and mechanical properties of wood plastics, i.e. specific gravity, moisture content, water absorption, shrinkage/ swelling, compression parallelto the wood grain, MOR and MOE. Greater use of vinyl acetate decreased physical and mechanical properties.